Response of encapsulated cells to a gelatin matrix with varied bulk and microenvironmental elastic properties†. (6th October 2016) - Blocki, Anna; Löwenberg, Candy; Jiang, Yi; Kratz, Karl; Neffe, Axel T.; Jung, Friedrich; Lendlein, Andreas
Abstract : Gelatin‐based hydrogels offer various biochemical cues that support encapsulated cells and are therefore suitable as cell delivery vehicles in regenerative medicine. However, besides the biochemical signals, biomechanical cues are crucial to ensure an optimal support of encapsulated cells. Hence, we aimed to correlate the cellular response of encapsulated cells to macroscopic and microscopic elastic properties of glycidylmethacrylate (GMA)‐functionalized gelatin‐based hydrogels. To ensure that different observations in cellular behavior could be attributed to differences in elastic properties, an identical concentration as well as degree of functionalization of biopolymers was utilized to form covalently crosslinked hydrogels. Elastic properties were merely altered by varying the average gelatin‐chain length. Hydrogels exhibited an increased degree of swelling and a decreased bulk elastic modulus G′ with prolonged autoclaving of the starting solution. This was accompanied by an increase of hydrogel mesh size and thus by a reduction of crosslinking density. Tougher hydrogels retained the largest amount of cells; however, they also interfered with cell viability. Softer gels contained a lower cell density, but supported cell elongation and viability. Observed differences could be partially attributed to differences in bulk properties, as high crosslinking densities interfere with diffusion and cell spreading and thus can impede cell viability. Interestingly, a microscopic elastic modulus in the range of native soft tissue supported cell viability and elongation best while ensuring a good cell entrapment. In conclusion, gelatin‐based hydrogels providing a soft tissue‐like microenvironment represent adequate cell delivery vehicles for tissue engineering approaches. Copyright © 2016 John Wiley & Sons, Ltd.